Measuring the Sociological Impact of Leadership Styles on Team Dynamics Among Library Staff in Private Universities in Edo State, Nigeria - Ossai-Ugbah, Ngozi Blessing; Sadoh, Lugard Ibhafidon (Communicate: Journal of Library and Information Science, 2025)
This study examined the sociological impact of leadership styles on team dynamics among library staff in private universities in Edo State, Nigeria. Drawing on Transformational Leadership Theory (Burns, 1978; Bass, 1985), Tuckman’s Group Development Model (1965), and Max Weber’s sociological theory of authority, the research explored how different leadership styles—transformational, transactional, and laissez-faire—affect team cohesion, communication, productivity, and job satisfaction in academic libraries. The study adopted a mixed-methods approach, combining quantitative survey data (n=54) with qualitative insights across four private universities: Benson Idahosa University, Wellspring University, Igbinedion University, and Glorious Vision University. Quantitative findings, analysed using SPSS v27.0, reveal that transformational leadership is the most prevalent style (77.8%), associated with higher levels of team cohesion, interpersonal trust, conflict resolution effectiveness, and job satisfaction. In contrast, laissez-faire leadership was not reported among the sampled institutions, while transactional leadership showed moderate influence, particularly in task execution and job performance. Statistical analysis (Fisher’s exact test, p=0.311) found no significant relationship between perceived leadership style and productivity levels, suggesting that other sociocultural factors may moderate this association. Qualitative responses underscored the importance of communication, staff motivation, conflict resolution, and emotional intelligence as key leadership attributes that enhance team dynamics. Recommendations include integrating transformational leadership training, promoting collaborative technologies, instituting staff well-being policies, and reinforcing merit-based reward systems. This research contributes to leadership and organisational studies within academic settings by highlighting context-specific leadership dynamics in Nigerian private universities. It offers actionable strategies for library managers to enhance team performance, foster positive workplace culture, and support institutional effectiveness through contextually responsive leadership practices.